The use of electronic information services (EIS) by undergraduate nursing students at the University of Namibia's (UNAM) northern campus : a descriptive study - Ndinoshiho, Joseph Megameno (Library and Information Studies Centre (LISC), 2015)
Includes bibliographical references (leaves 171-187).